2021
DOI: 10.1002/saj2.20194
|View full text |Cite
|
Sign up to set email alerts
|

Fine grinding is needed to maintain the high accuracy of mid‐infrared diffuse reflectance spectroscopy for soil property estimation

Abstract: Core ideas: 1. Effect of fine grinding (FG) on MIR model performance variation was studied. 2. Five model calibration-validation schemes and 2 modeling techniques were tested. 3. Best performance was obtained when FG library models were used on FG samples. 4. Predictions on FG spectra always outperformed non-ground spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Reduce the costs of analyses and enable higher throughput Baldock et al, 2014;Wijewardane et al, 2018Wijewardane et al, , 2020Dangal et al, 2019;Yu et al, 2020 Improves baselining and reduces model uncertainty to generate high-value credits New metrics for soil health Earlier identification of practices that have an impact on soil carbon sequestration Conant et al, 2011;Cotrufo et al, 2015;Vos et al, 2018;Lavallee et al, 2020 inorganic carbon amendments such as biochar to enhance carbon sequestration, provided that the carbon remains in the project area. Properly quantifying and verifying the inorganic carbon stocks, however, is challenging as it is not currently estimated by biogeochemical models.…”
Section: Improved Lab Analytical Methodsmentioning
confidence: 99%
“…Reduce the costs of analyses and enable higher throughput Baldock et al, 2014;Wijewardane et al, 2018Wijewardane et al, , 2020Dangal et al, 2019;Yu et al, 2020 Improves baselining and reduces model uncertainty to generate high-value credits New metrics for soil health Earlier identification of practices that have an impact on soil carbon sequestration Conant et al, 2011;Cotrufo et al, 2015;Vos et al, 2018;Lavallee et al, 2020 inorganic carbon amendments such as biochar to enhance carbon sequestration, provided that the carbon remains in the project area. Properly quantifying and verifying the inorganic carbon stocks, however, is challenging as it is not currently estimated by biogeochemical models.…”
Section: Improved Lab Analytical Methodsmentioning
confidence: 99%
“… Nduwamungu et al (2009) did not find improvements in predictions from < 2 mm soil samples for the NIR range. Both LeGuillou et al (2015) and Wijewardane et al (2020) reported that predictions from fine ground samples always outperformed those from non-fine ground for the MIR region. Results in this study align with the literature.…”
Section: Resultsmentioning
confidence: 97%
“…A number of studies have researched these effects for (V)NIR/MIR soil spectroscopy. For example, studies analysed the effect of different particle sizes ( Nduwamungu et al, 2009 , LeGuillou et al, 2015 , Coutinho et al, 2019 , Wijewardane et al, 2020 ), soil water content ( Bogrekci and Lee, 2006 , Minasny et al, 2011 , Ji et al, 2015 ) and in-field (V)NIR measurements ( Stevens et al, 2008 ; Gras et al, 2014 ) on soil spectroscopy predictions.…”
Section: Introductionmentioning
confidence: 99%
“…The latter qualification is relevant given the importance of sample pre-treatment for the accuracy and reproducibility of VNIR and MIR measurements and derived SOC models [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Fine-grinding generally increases predictive accuracies and is especially relevant for MIR spectroscopy, where the amount of scanned soil material is lower and thus likely less representative without careful homogenization due to smaller beam apertures and shallower penetration depths for MIR instrumentation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%